GSK-3 and Wnt Signaling in Neurogenesis and Bipolar Disorder - Valvezan, Alexander J.; Klein, Peter S. (Frontiers in Molecular Neuroscience, 2012)
The canonical Wnt signaling pathway is critical for development of the mammalian central nervous system and regulates diverse processes throughout adulthood, including adult neurogenesis. Glycogen synthase kinase-3 (GSK-3) antagonizes the canonical Wnt pathway and therefore also plays a central role in neural development and adult neurogenesis. Lithium, the first line of therapy for bipolar disorder, inhibits GSK-3, activates Wnt signaling and stimulates adult neurogenesis, which may be important for its therapeutic effects. GSK-3 also regulates other critical signaling pathways which may contribute to the therapeutic effects of lithium, including growth factor/neurotrophin signaling downstream of Akt. Here we will review the roles of GSK-3 in CNS development and adult neurogenesis, with a focus on the canonical Wnt pathway. We will also discuss the validation of GSK-3 as the relevant target of lithium and the mechanisms downstream of GSK-3 that influence mammalian behavior.